SMARTVINO project: When wine can benefit from ICT - Andrea Del Mastio; Roberto Caldelli; Matteo Casini; Martino Manetti (Wine Economics and Policy, 2016)
SMARTVINO project is devoted to the study and implementation of innovative services able to convey information related to wine and its traceability to costumers and consumers. The basic idea is to realize a simple and user-friendly tool, addressed to all kind of users and therefore immediately effective for everyone. SMARTVINO system allows users to take a photo of the previously marked company logo, depicted on the wine label, by a ordinarily known smartphone and then redirected to lots of detailed information related to the wine they are buying or drinking. Contents can concern the productive process, the vine variety the wine is made by, the geo-spatial localization of the vineyards, recommendations about which course is the most appropriate to be coupled with the wine, etc; in general, all the information or suggestions the producing winery wants to share with its customers. Such information can be in form of text, images, videos and web pages. The project is still on-going at the date of writing. Next activities will be dedicated to draft a detailed plan for the commercial use of results. This paper is devoted to present the outcomes of the project and how these can be exploited in wine scenario.
Keywords: 330; ICT; Smartphone; Wine